"أثر الآليات المحاسبية لحوكمة الشركات في تحسين الأداء المالي لدعم القدرة التنافسية للمؤسسات المالية" - دراسة ميدانية (Economic studies journal, 2023)
The study aimed to know the impact of the accounting mechanisms of corporate governance in improving financial performance to support the competitiveness of financial institutions on a sample of the research community of the State Audit Institution, and the researcher relied on the inductive and deductive approach to achieve the objectives of the research through the research community represented by the 230 auditors working in the State Audit Institution. According to the information available to the researcher, the research sample was selected in a simple random way from among the 80 members of the research community, and the questionnaire was distributed to them and 70 questionnaires used in the analysis were returned.The research reached the most important result, which is: The results of the research showed that there is a statistically significant relationship that the accounting mechanisms are applied (the mechanism of the company's commitment to applying disclosure and transparency of financial reports, accounting and auditing standards - the internal audit mechanism - the mechanism of the role of the external auditor - the mechanism of the independence of the audit committees) and improving Financial performance to support competitiveness.
Keywords: Accounting standards; Internal auditor; Financial performance; Competitiveness; Corporate governa nce